Impact of work-rest period on mental fatigue in inspection task with microscope: Case study of hard disk drive component manufacturing company - Rungchat Chompu-Inwai (2018)
In recent years, inspection has declined in importance as statistical process control has assumed a more prominent role in the quality function. However, product quality inspection is still an important task in the production of hard disk drive component manufacturing. In the case study company, which produces hard disk drive component, inspection occurs at many points in a process. Inspectors perform 100% inspection using microscope for many hours without adequate break. After continually monitoring the performance of inspectors, it was found that certain nonconformities were more difficult to find, the number of nonconformities reported was unusual, and inspectors varied in their abilities. Turnover rate of the quality inspection division in this company is high. Therefore, this research aims at determining the impact of working duration and resting time on reducing the mental fatigue in inspection task with microscope in the hard disk drive component manufacturing. Five types of working duration and resting time were studied and compared using Randomized Complete Block Design of Experiment with two replicates. A variety of data collection tools were used to assist in the data collection. The data collection tools used included bipolar questionnaire, reaction time, and critical flicker frequency (CFF). The analysis of variance (ANOVA) was conducted. The result showed that, the work-rest period type significantly affects the mental fatigue reduction as measured by questionnaire scores and reaction time. However, the work-rest period type significantly does not affect the mental fatigue reduction as measured by CFF.